2002
DOI: 10.1002/ijc.10444
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in a population‐based cohort of patients with Wegener's granulomatosis

Abstract: Wegener's granulomatosis is necrotizing granulomatous vasculitis of unknown origin, which untreated has a high mortality within the first year of onset. The introduction of corticosteroids and cyclophosphamide in the treatment has considerably improved survival rates, but past studies have indicated an increased cancer risk, including an increased risk for urinary bladder cancer. No large assessment of the general cancer occurrence in Wegener's granulomatosis has been reported. The aim of our study was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
4
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(155 citation statements)
references
References 24 publications
7
140
4
4
Order By: Relevance
“…When kidney involvement was stratified according to sex, males presented with kidney involvement more frequently than females (57.8% versus 40.1%; P Ͻ 0.001). The median DEI at diagnosis and over the whole disease course was higher in males (at diagnosis, 9 [range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]; P ϭ 0.001). The median time to diagnosis after the occurrence of first symptoms was 6 months (range 0-250 months) for young males and 11 months (range 0-195 months) for young females (P ϭ 0.47).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…When kidney involvement was stratified according to sex, males presented with kidney involvement more frequently than females (57.8% versus 40.1%; P Ͻ 0.001). The median DEI at diagnosis and over the whole disease course was higher in males (at diagnosis, 9 [range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]; P ϭ 0.001). The median time to diagnosis after the occurrence of first symptoms was 6 months (range 0-250 months) for young males and 11 months (range 0-195 months) for young females (P ϭ 0.47).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Several large-scale studies demonstrated that cases with AAV developed malignancies 1.6-2.4 times as often as the general population [7][8][9][10][11] . Randomized controlled trials (RCTs) and long-term follow-up (LTFU) studies in Western countries showed that malignancies were observed in 12.6% of MPA cases and 10.8% in cases of granulomatosis with polyangiitis (GPA) during the 87-month follow-up period after treatment for vasculitis 12)18-21) .…”
Section: Discussionmentioning
confidence: 99%
“…Primary vasculitis, polyarteritis nodosa, anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), and IgA vasculitis also frequently coincide with malignancies [2][3][4][5] . In cases of AAV, immunosuppressants such as cyclophosphamide are administered for treatment after diagnosis, and it is reported that malignancies develop more often in such cases than in the general population [6][7][8][9][10][11][12][13] . This may suggest that immunosuppression treatment carries an inherent risk of increased cancer rates in those with AAV.…”
Section: Introductionmentioning
confidence: 99%
“…The most important adverse effect was the occurrence of solid cancer observed in 6 patients, all belonging to the cyclophosphamide+etanercept group. The incidence of solid cancer has been reported to be 2-6 times higher in patients with Wegener's granulomatosis compared with gender-and age-matched general population, 4,5) and the cyclophosphamide administration has been known to increase in the incidences of bladder cancer and hematologic malignancies. However, the 6 patients consisted of 2 with mucous adenocarcinoma and 1 each with bile duct cancer, kidney cancer, breast cancer, and liposarcoma, which differed from cyclophosphamide-related tumors.…”
Section: Usefulness Of Infliximab For the Treatment Of Anca-associatementioning
confidence: 99%